2012
DOI: 10.1016/j.jpha.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of pioglitazone and candesartan in human plasma by LC-MS/MS and its application to a human pharmacokinetic study

Abstract: A simple and rapid liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method has been developed and fully validated for simultaneous quantification of pioglitazone and candesartan in human plasma. Irbesartan was used as an internal standard. The analytes were extracted from human plasma samples by solid-phase extraction technique using a Strata-X 33 μm polymeric sorbent. The reconstituted samples were chromatographed on a C18 column by using a 80:20 (v/v) mixture of acetonitrile and 0.1% formic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Another LC/MS/MS study was reported by Kumari Karra et al [71] for simultaneous determination of PIO and candesartan in human plasma in which Irbesartan was used as an internal standard. Solid phase extraction was used for extracting the analytes from plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Another LC/MS/MS study was reported by Kumari Karra et al [71] for simultaneous determination of PIO and candesartan in human plasma in which Irbesartan was used as an internal standard. Solid phase extraction was used for extracting the analytes from plasma.…”
Section: Methodsmentioning
confidence: 99%
“…The precursor → product ion transitions (MRM) of PGZ and IS was m / z 357.95 → 135.15 and m / z 358.00 → 94.05, respectively, which were in agreement with the previous reports. 26–30 …”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed several bio‐analytical methods reported for ROS (Braga, Mancila, Cassella, & Pacheco, ; Caglar & Toker, ; Darwish & Al‐malaq, ; J. Gao, Zhong, Duan, & Chen, ; C K Hull, Penman, Smith, & Martin, ; Caroline K. Hull, Martin, Warwick, & Thomas, ; Hussain, Patel, & Tan, ; Kallem, Karthik, Chakradhar, & Mullangi, ; T. R. Kumar et al, ; Lan et al, ; H. K. Lee, Ho, Hu, Tomlinson, & Wong, ; MacWan, Ionita, & Akhlaghi, ; Oudhoff, Sangster, Thomas, & Wilson, ; Xu, Ruan, Yuan, & Jiang, ) and CAN (Gao et al, ; Jeon et al, ; Kondo, Yoshida, Yoshimura, Motohashi, & Tanayama, ; J. W. Lee et al, ; Lou, Ruan, & Jiang, ; Miyabayashi, Okuda, Motohashi, Izawa, & Yashiki, ; Prajapati, Patel, Chauhan, Patel, & Patel, ; Stenhoff, Lagerström, & Andersen, ) individually or in combination with other drugs like pioglitazone, hydrochlorothiazide, ciprofloxacin, metformin, etc., using either HPLC or LC–MS/MS (Arayne, Sultana, & Tabassum, ; Pp. Kumar, Murthy, & Basaveswara Rao, ; Narapusetti, Bethanabhatla, Sockalingam, Repaka, & Saritha, ; Nasir et al, ; Shah et al, ; Trivedi, Kallem, Mullangi, & Srinivas, ; Varghese & Ravi, ; Vittal et al, ; Bharathi, Hotha, Chatki, Satyanarayana, & Venkateswarlu, ; Gonzalez, Lopez, Alonso, & Jimenez, ; Kumari Karra, Rao Pilli, Kumar Inamadugu, & Seshagiri Rao, ; Nie et al, ; Singh, Lokhandae, Dwivedi, Sharma, & Dubey, ).…”
Section: Introductionmentioning
confidence: 99%